In The Media: Expanding Students' Experience With Academic Vocabulary. (23rd August 2013) - McKeown, Margaret G.; Crosson, Amy C.; Artz, Nancy J.; Sandora, Cheryl; Beck, Isabel L.
Abstract: How can we supplement the limited time available for vocabulary instruction while motivating students to attend to the words they are learning? As a part of an academic word vocabulary intervention, we challenged sixth‐grade students to find their words in the world around them. This activity, In the Media, garnered responses from 51 of the 61 students involved in the intervention. Analysis of students' reading comprehension achievement showed that it was not just high‐achieving students who responded; rather the full range of achievement was represented. Analysis of pretest and posttest data revealed that students who found more words had the highest gains in the final assessment. Examples of students' encounters and where they found them are discussed. These examples suggest that students developed flexible knowledge of their words, as they were able to find them in uses beyond those taught and in related forms that had not been introduced.